Prevenção secundária do câncer do trato aerodigestivo superior por meio da estratégia de busca ativa e uso da propedêutica armada - Santos, Francis Balduino Guimaraes [UNIFESP] (2017)
Introduction: The upper aerodigestive tract cancer is among the most frequent types and presents itself with epidemiological importance in the world. Most are advanced to diagnosis, with a strong negative impact on survival and high cost to the public. The campaigns against these types of cancer have systematically failed in Brazil. Objective: To evaluate the effectiveness of screening for upper aerodigestive tract cancers, using active search strategies and use of armed propaedeutics. Method: A cross-sectional, prospective, descriptive, analytical and exploratory study, since its objectives are based on the description of the cancerous lesions in a sample of 603 individuals, in order to deepen the knowledge necessary for its detection with a view to secondary prevention of the oral cavity, oropharynx, larynx and hypopharynx cancers. Result: 101 (16.7%) cancerous lesions and 3 (0.5%) localization cancers in the upper aerodigestive tract were diagnosed by clinical method. Conclusion: The method was effective in the identification of precursor lesions with the aim of secondary prevention, but equally important against cancer, since in this present study more than tripled (3.6x more) the chance of the disease finding, being then the model for future campaigns against upper aerodigestive tract cancer.